Missing and Delayed Auditory Responses in Young and Older Children with Autism Spectrum Disorders - Edgar, J. Christopher; Lanza, Matthew R.; Daina, Aleksandra B.; Monroe, Justin F.; Khan, Sarah Y.; Blaskey, Lisa; Cannon, Katelyn M.; Jenkins, Julian; Qasmieh, Saba; Levy, Susan E.; Roberts, Timothy P. L. (Frontiers in Human Neuroscience, 2014)
Background: The development of left and right superior temporal gyrus (STG) 50ms (M50) and 100ms (M100) auditory responses in typically developing children (TD) and in children with autism spectrum disorder (ASD) was examined. It was hypothesized that (1) M50 responses would be observed equally often in younger and older children, (2) M100 responses would be observed more often in older than younger children indicating later development of secondary auditory areas, and (3) M100 but not M50 would be observed less often in ASD than TD in both age groups, reflecting slower maturation of later developing auditory areas in ASD. Methods: 35 typically developing controls, 63 ASD without language impairment (ASD-LI), and 38 ASD with language impairment (ASD+LI) were recruited.The presence or absence of a STG M50 and M100 was scored. Subjects were grouped into younger (6 to 10-years-old) and older groups (11 to 15-years-old). Results: Although M50 responses were observed equally often in older and younger subjects and equally often in TD and ASD, left and right M50 responses were delayed in ASD-LI and ASD+LI. Group comparisons showed that in younger subjects M100 responses were observed more often in TD than ASD+LI (90% vs 66%, p=0.04), with no differences between TD and ASD-LI (90% vs 76% p=0.14) or between ASD-LI and ASD+LI (76% vs 66%, p=0.53). In older subjects, whereas no differences were observed between TD and ASD+LI, responses were observed more often in ASD-LI than ASD+LI. Conclusions: Although present in all groups, M50 responses were delayed in ASD, suggesting delayed development of earlier developing auditory areas. Examining the TD data, findings indicated that by 11 years a right M100 should be observed in 100% of subjects and a left M100 in 80% of subjects. Thus, by 11years, lack of a left and especially right M100 offers neurobiological insight into sensory processing that may underlie language or cognitive impairment.